Electrophysiological and biophysical perspectives on the clitoral corpus cavernosum and its role in female sexual arousal disorder - Mahapatra, Chitaranjan; Raiguru, Jagatpati; Lakshminarasimha, Kasetty; Al-Emam, Ahmed; Rusho, Maher Ali (Frontiers in Physiology, 2025)
The clitoris is a vital part of the female sexual system, playing a crucial role in sexual satisfaction and overall sexual health. During arousal, the smooth muscle within the corpus cavernosum of the clitoris relaxes, which increases blood flow and causes the clitoral tissues to swell and firm. This vascular engorgement is not only essential for clitoral erection but also enhances the pleasurable sensations during sexual activity. However, conditions such as pelvic floor disorders, Peyronie’s disease, neuromuscular disorders, and hormonal imbalances can lead to dysfunction in the smooth muscle of the corpus cavernosum, significantly impacting female sexual function. The contractile behavior of these smooth muscles is governed by intricate cellular and subcellular processes, particularly the generation of intracellular electrical activities, with calcium influx playing a central role. This calcium influx is mediated through voltage-dependent calcium channels and calcium release from intracellular stores. Despite the critical importance of these mechanisms, comprehensive studies on the biophysical aspects of smooth muscle electrophysiology are limited, likely due to their complexity. This review seeks to investigate the cellular electrophysiological mechanisms underlying the electrical excitability of corpus cavernosum smooth muscle and to understand the biophysical aspects of clitoral muscle contraction disorders. It also proposes a first conceptual model to guide future research, with the aim of supporting the development of more effective treatments and enhancing female sexual health.